Parent-School Collaboration in Online Curriculum Design for Non-formal Schools in East Java Province, Indonesia: A Design-Based Research - Robianti, Febi; Raufu, Mufutau; Amalia, Nurul; Nasution, Dini (Indonesian Journal Publisher, 2025)
This study explores the dynamics of parent-school collaboration in the design of online curricula for non-formal education institutions in East Java Province, Indonesia. Against the backdrop of increasing reliance on digital learning platforms, particularly within community-based educational centers like PKBM, the research addresses a critical gap in understanding how parental involvement can enhance the relevance, accessibility, and effectiveness of online learning. Guided by theories on parenting, educational design, and cultural contextualization, the study adopts a qualitative design-based research approach. Using purposive sampling, data were collected through in-depth interviews, focus group discussions, and document analysis involving educators, parents, and administrators from selected non-formal schools. Thematic analysis revealed several key findings: (1) parent-school collaboration significantly improves curriculum contextualization by incorporating cultural and familial values; (2) communication channels and engagement strategies require structured facilitation to be effective; and (3) such collaboration positively impacts student engagement and learning outcomes. The study concludes that meaningful stakeholder engagement, especially with parents, is essential for tailoring online curricula in non-formal settings, thereby offering a sustainable model for inclusive education across diverse communities in Indonesia.